A finite-element-based approach to quantify the impact of bed joint reinforcement on the compressive strength of vertically perforated clay block masonry. (15th July 2021) - Suda, Raphael; Kiefer, Thomas; Schranz, Christian; Füssl, Josef
Highlights: Accurate strength predictions for clay block masonry with reinforced bed joints. Combination of continuum micromechanics with extended finite element method. Reliable quantification of strength increase due to bed joint reinforcement. Experimentally validated prediction tool, including stochastic aspects. Abstract: Since lateral tensile stresses trigger failure of vertically perforated clay block masonry under vertical loading, reinforcement of the bed joints introduces a new way to improve the vertical resistance of masonry. The aim of this work is to estimate the feasible increase of the vertical compressive strength by means of the eXtended Finite Element Method (XFEM). Using a unit cell approach and a stochastic strength distribution, the increase of the masonry strength's 5%-quantile could be predicted with 33%. Hence, this work constitutes the vast potential of fibre reinforced bed joints in improving the vertical compressive strength of clay block masonry.